In-store communication of reusable bag: Application of goal-framing theory - Ayu Ekasari (Jurnal Manajemen dan Pemasaran Jasa, 2021)
Campaigns on pro-environmental behavior are an important objective in social marketing due to the environmental problems caused by people's consumption. Therefore, social marketers need to understand the underlying factors that make people change their behavior. This research investigates the determinants of pro-environmental behavior from the perspective of goal framing theory with three overarching goals, namely hedonic, gain, and normative. The data were collected using a questionnaire survey method and analyzed by structural equation modeling. The results showed that gain and normative goals directly affect pro-environmental behavior instead of a hedonic goal. This research also showed that the biospheric value as one of the self-transcendence values moderates the effect of normative goal towards pro-environmental behavior, proposed in preliminary studies. The findings contribute to the existing research regarding pro-environmental behavior determinants and used by social marketing initiatives, especially in-store-communication, in designing the right message. Future studies need to investigate the role of hedonic and egoistic values in predicting pro-environmental behavior.